HUBUNGAN KEPRIBADIAN DENGAN SMARTPHONE ADDICTION PADA SISWA DI SMKN 01 SURABAYA - Nety Mawarda Hatmanti; Febriarta, Ajie; Hanik, Umi; Noventi, Iis (JURNAL KEPERAWATAN, 2023)
Background: Various human personalities will affect a person's response to the surrounding environment. One of the personality traits, namely difficulty getting along, is afraid that it will have an impact on others, one of which is Smartphone addiction. Objective: To analyze the relationship between personality and Smartphone addiction in adolescents. Methods: This study used an observational analytic design with a cross-sectional study. Non-probability sampling technique is used to obtain a sample. The population of this study were all students at SMKN 01 Surabaya, totalling 800 respondents and a total sample of 267 respondents was obtained using the simple random sampling technique. The independent variable is personality. The dependent variable is Smartphone addiction. Research data was collected by distributing questionnaires in the form of a Google form, followed by data analysis using the Spearman Rank test. Results: This study shows that the majority (71.5%) of respondents have an adequate level of personality, the majority (67.4%) have a moderate level of Smartphone addiction, and based on statistical tests the results obtained are ρ = 0.02 which means there is a relationship between personality and Smartphone addiction. Conclusion: Personality is related to Smartphone addiction in adolescents. Various roles and support are needed both at home and at school to continue to accompany children in using Smartphones. If personality is directed in a good direction, it will reduce the impact of the effect on Smartphone use. Keywords : Adolescents; Personality; Smartphone addiction